A Review of Deterministic Optimization Methods in Engineering and Management - Lin, Ming-Hua; Yu, Chian-Son; Tsai, Jung-Fa (Mathematical Problems in Engineering, 2012)
With the increasing reliance on modeling optimization problems in practical applications, a number of theoretical and algorithmic contributions of optimization have been proposed. The approaches developed for treating optimization problems can be classified into deterministic and heuristic. This paper aims to introduce recent advances in deterministic methods for solving signomial programming problems and mixed-integer nonlinear programming problems. A number of important applications in engineering and management are also reviewed to reveal the usefulness of the optimization methods.